Three essays on health economics - Carrillo Bermudez, Bladimir (2017)
This thesis studies three topics on health economics using Brazilian data. In the first essay, we study the effects of low birth weight on infant mortality. Understanding such a relationship is important for the development of policies aimed at reducing the incidence of infant mortality. However, it is little known about this topic in developing countries and estimates from rich economies may have limited external validity to the developing world. Our empirical strategy to isolate the effect of low birth weight from other determinants of infant mortality exploits within-twin variation. The results indicate that lower birth weight babies exhibit higher rates of mortality within one year of birth. The effects are much larger than those derived from the US and Norwegian context. The second essay provides the first estimates of the local externalities of deforestation in infant health. The burning of forest releases a wide range of contaminants, some of which are known to be hazardous for health. Traditional estimates of the costs of deforestation rarely incorporate the health effects of pollution generated by deforestation. For identification, we use the large and heterogeneous reductions in deforestation across sites in the Brazilian Amazon generated by a conservation policy. The findings suggest that deforestation control policy led to reductions in the incidence of low birth weight and prematurity. This is especially true for boys. Collectively, these results provide additional justification for controlling deforestation. Finally, the third essay estimates the effect of increased supply of physicians on child hospitalizations. It is a widely held position that spending resources on increasing the availability of physicians is an effective way to improve child health. However, there is very little rigorous investigation documenting the quantitative importance of physicians for child health. Our empirical strategy exploits a dramatic increase in the number of physicians generated by the Mais Medico program to fill this gap. The results suggest that program implementation is associated with statistically significant reductions in avoidable, ambulatory sensitive hospitalizations only in poor areas. Our estimates indicate that policy lead to a fall of 4.8 percent in avoidable child hospitalizations. Together, the three essays contribute to a better understanding about vi the causes of poor health in early life using data from Brazilian, a rapidly emerging economy.